Synthesis and Characterization of Novel Nano-carbon Mixture from Dabai (Canarium odontophyllum) Nutshell - Anthonette, James; Md Rezaur, Rahman; Durul, Huda; Faisal M., Aqlan; Mohammed Mahbubul, Matin; Muhammad Khusairy, Bakri; Kuok King, Kuok; Mohammed Muzibur, Rahman (NC State University, 2022)
The nanocarbon-based mixture was shown to be an effective adsorbent for removing dyes and heavy metals from wastewater via adsorption. The goal of this research was to prepare and investigate the properties of a bio-carbon mixture made from Dabai (Canarium odontophyllum) nutshell with the addition of titanium dioxide (TiO2) and montmorillonite (MMT) clay. Fourier transform infrared (FTIR) spectroscopy was used to determine the functional groups of raw carbon and potassium hydroxide (KOH)-activated carbon (AC). The FTIR analysis of the active carbon revealed that the active carbon had more surface chemistry than the non-AC. Scanning electron microscopy (SEM) analysis was used to compare the raw and AC morphologies and the developed nanocarbon. The results were confirmed using energy dispersive X-ray (EDX) analysis to verify the elements in the studied sample. The SEM analysis revealed that the structure of both the carbon samples was irregular, granular, and porous. BET analysis showed that nano-activated carbon had higher surface area compared to activated carbon itself. Response surface methodology (RSM) was used in DesignExpert 13.0 software for the sample composition development to achieve the best performance of the developed nanocarbon as an adsorbent.